Поняття кадрового забезпечення Державної митної служби України - Колобиліна, О. О.; Kolobylina, O. O. (Право.ua. - 2023. - № 4, ч. 2. - С. 182-187, 2023)
У статті обґрунтовано важливість та необхідність здійснення якісного та ефективного кадрового забезпечення Державної митної служби України, як особливого органу державної влади. Спираючись на аналіз наукових поглядів вчених розкрито загальнотеоретичні підходи щодо тлумачення понять кадри та кадрове забезпечення, на основі чого запропоновано авторське бачення тлумачення «кадрового забезпечення Державної митної служби України».

The most important features that characterize the term “personnel support” are highlighted: firstly, this concept describes a special, complex procedural and organizational activity of an enterprise, institution, organization, which is carried out by the employer directly or by a specially authorized structural unit, with the aim of forming a high-quality and effective personnel; secondly, personnel support has a clearly defined goal, which involves solving the following tasks: 1) streamlining the work of the personnel of the enterprise, institution, organization; 2) provision and protection of his basic labor rights and interests; 3) professional education and training of employees in accordance with the goals of the work of a certain entity, as well as the internal specifics of its work; 4) search, selection and appointment of new personnel who are suitable for work in certain conditions according to their moral, psychological, professional and other qualities; 5) analysis, planning and control of personnel processes, determination of prospects for their development, as well as ways of improving the latter; thirdly, staffing is a regulatory activity that takes place in strict accordance with the general legislative and local legal norms that regulate the activity and internal labor or service relations of a particular enterprise, institution or organization; fourthly, personnel support finds its manifestation in a set of special forms, as well as a set of methods inherent in the work of a certain subject in a specific sphere of social life.

В статье обоснована важность и необходимость осуществления качественного и эффективного кадрового обеспечения Государственной таможенной службы Украины как особого органа государственной власти. Опираясь на анализ научных взглядов ученых раскрыты общетеоретические подходы к толкованию понятий кадры и кадровое обеспечение, на основе чего предложено авторское видение толкования «кадрового обеспечения Государственной таможенной службы Украины».
Keywords: кадри; кадрове забезпечення; державна служба; Державна митна служба України; personnel; personnel support; state service; State Customs Service of Ukraine; кадры; кадровое обеспечение; государственная служба; Государственная таможенная служба Украины